2016
DOI: 10.1186/s12909-016-0681-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception and knowledge of evidence based medicine by physicians

Abstract: BackgroundThe influence, legitimacy and application of Evidence Based Medicine (EBM) in the world is growing as a tool that integrates, the best available evidence to decision making in patient care. Our goal was to identify the relationship between self-perception about the relevance of Evidence Based Medicine (EBM) and the degree of basic knowledge of this discipline in a group of physicians.MethodsA survey was carried out in a third level public hospital in Mexico City. Self-perception was measured by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…Similar results were previously reported regarding the EBM self-assessment as well as the utility of evidencebased practice and the use of the EBM concept in the daily activity [5,28]. Our study also reveals disagreement between how the respondents perceived their own EBM knowledge and their actual knowledge ( Table 2, A01, A03, A04, A05).…”
Section: Knowledge Awareness and Attitudessupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were previously reported regarding the EBM self-assessment as well as the utility of evidencebased practice and the use of the EBM concept in the daily activity [5,28]. Our study also reveals disagreement between how the respondents perceived their own EBM knowledge and their actual knowledge ( Table 2, A01, A03, A04, A05).…”
Section: Knowledge Awareness and Attitudessupporting
confidence: 87%
“…Aguirre-Raya et al reported in 2016 the perception of EBM among medical students, interns, and specialists and reported a high global index of self-perception (75%), but this proved not to be supported by the global index on knowledge (19%) [5]. The gap between the attitude towards EBM and knowledge and awareness has been reported among physicians from different parts of the world (e.g., Saudi Arabia [6], United Arab Emirates [7], Ethiopia [8], Egypt [9], Japan [10], Belgium [11], Norway [12], France [13], or India [14]).…”
Section: Introductionmentioning
confidence: 97%
“…This is while self‐reported (perceived) knowledge has been shown to be significantly different from actual knowledge. This fact may reflect that the results of the studies in this systematic review may be an overestimation of the actual knowledge level of physicians …”
Section: Discussionmentioning
confidence: 93%
“…A major discrepancy between physician's self‐perception and the level of basic knowledge of EBM is persistently shown, with doctors overestimating benefits, underacknowledging harms and poorly communicating this to patients (Aguirre‐Raya et al., ; Krouss, Croft & Morgan, ). In terms of ‘treatment’, absolute risk reductions are not systematically demanded by editors or provided in national formularies and guidelines.…”
Section: Evidence‐based Medicine and Shared Understanding Of Medicinementioning
confidence: 99%